New avenue of diagnostic stewardship: procedural stewardship for recurrent urinary tract infections in female patients - Tanner D. Corse; Linda Dayan Rahmani; Hunter L. Hasley; Katherine Kim; Robert Harrison; Debra L. Fromer (Cambridge University Press, 2023)
Abstract Introduction: Societal guidelines offer a weak recommendation to perform cystoscopy for female patients with recurrent urinary tract infections (rUTI) of advanced age and/or with high-risk features. These guidelines lack the support of robust data and are instead based on expert opinion. In this retrospective cohort study, we aim to determine the utility of cystoscopy in patients with and without high-risk features for rUTI. Materials and methods: We identified 476 women who underwent cystoscopy for the evaluation of rUTI at a single tertiary academic medical center from May 1, 2015 and March 15, 2021. Patients were excluded if they had a competing indication for cystoscopy. Risk factors, demographic information, cystoscopic findings, and patient outcomes were analyzed. Results: 192 (41.1%) were classified as having complicated UTI. We identified six patients (1.3%) with findings that prompted management to significantly impact patient outcomes. All six patients had high-risk features. 14 patients (3.0%) were found to have mucosal abnormalities prompting biopsy, three of which required general anesthesia. All 14 biopsies were ultimately benign. Conclusions: Our findings demonstrate a low diagnostic yield and increased risk exposure for women undergoing cystoscopy for the evaluation of complicated rUTI. Additionally, our observations support prior studies indicating that cystoscopy has limited utility in the evaluation of rUTI without high-risk features.